Arquitetura e arqueologia industrial em Minas Gerais: o período inglês - Lizandro Edmundo Cordeiro de Melo Franco (2002)
This work is concerned with some characteristics of both architecture and urbanism related to industrial activities in Minas Gerais, in particular with the English presence in mining settlements during the 19th and early 20th Centuries. The analysis is based on the comprehension of British references of the same era applied to two specific cases: the urban and architectural experience of Morro Velho and the industrial archaeology of Gongo Soco. The main goal is the identification of the nature of such interpenetration of cultures and the hybridism of languages, also the relevance and configuration of these features in local architectural production.